Impact of fitness coach behavior on exercise motivation, commitment, and enjoyment: A longitudinal study. - Ricardo Braga-Pereira; Guilherme Eustáquio Furtado; Francisco Campos; António Rodrigues Sampaio; Pedro Teques (PLoS ONE)
Fitness coaches seem to play an essential role in the field of exercise as they help prevent sedentary lifestyles and promote overall health, quality of life, and well-being. This study aimed to explore the effects of fitness coaches' behavior perceptions, intrinsic motivation, and enjoyment of exercisers on their long-term fitness and health, as well as their commitment to exercise. A total of 202 individuals participated in the study that was developed over three data gathering occasions (baseline, three months and six months). To this end, three psychometric scales were used as part of a multi-section survey: FCBS-Fit (perception of the fitness coach's behavior), IMIp (intrinsic motivation of exercisers), and PACES (enjoyment in exercise), along with the assessment of four health/fitness variables: anthropometry (i.e., waist-hip ratio), strength (i.e., handgrip strength), flexibility (i.e., sit-and-reach), and cardiorespiratory fitness (i.e., VO2máx.). Overall, the results suggested that the perception of the fitness coach's behavior, the exerciser's intrinsic motivation, and enjoyment were predictors of the health/fitness outcomes, and seemed to be related to the exercise commitment at the end of three and six months. The novelty of this study is the examination of psychological and physiological factors in an integrated and longitudinal manner within the scope of exercise in fitness and health clubs. Therefore, these findings shed light on fitness coaches as an important element in the propagation and maintenance of exercise habits, accomplishment of tangible outcomes by exercisers, health promotion and the fitness sector's growth.